Território, governança e desenvolvimento territorial: um estudo comparado entre Brasil e União Europeia - Silva, Filipe Prado Macedo (2017)
This work uses Brazil and the European Union as objects of study. In this sense, we seek to compare three themes/characteristics: (1) the (subnational) territories in Brazil and in the European Union; (2) governance in Brazil and in the European Union; and (3) public policies for territorial development in Brazil and in the European Union. Over the last 20 years, these three themes/characteristics have gained political, economic, and/or social importance in Brazil and in the European Union, and they have consolidated around international recommendations. However, despite the success of territorial public policies in Brazil and in the European Union, numerous obstacles and different controversies still permeate the delimitations and governance structures of the territories, revealing the complexity of the three themes/characteristics in question. It is in this context that the problem of this work arises: What are the main differences, similarities, and singularities between territories, governance, and public policies for territorial development in Brazil and in the European Union? To answer this question, the main objective of this work is to identify and analyze the main differences, similarities, and singularities between: (1) the territories in Brazil and in the European Union; (2) governance in Brazil and in the European Union; and (3) public policies for territorial development in Brazil and in the European Union. To perform this work, we adopted a qualitativecomparative study of international experiences (or cases) in search of both primary and secondary data. The result was that in Brazil and in the European Union, despite the differences, similarities, and singularities, territories have become the main objects of intervention regarding public policies for territorial development, and the governance structures have become the main dynamic processes from which the public policies of territorial development are forged.